2023
DOI: 10.31234/osf.io/u7s2b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the replicability of backfire effects after standalone corrections

Abstract: Corrections are a frequently used and effective tool for countering misinformation. However, concerns have been raised that corrections may introduce false claims to new audiences when the misinformation is novel. This is because boosting the familiarity of a claim can increase belief in that claim, and thus exposing new audiences to novel misinformation—even as part of a correction—may inadvertently lead to the formation of misconceptions. Such an outcome could be conceptualized as a familiarity backfire effe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This is in line with a number of other investigations that included source discreditation alongside contentfocussed corrections as an element of a successful debunking intervention (e.g., MacFarlane et al, 2021;Paynter et al, 2019;Tay et al, 2022). A recent study conducted in a simulated social-media environment found that the presence of source-credibility information boosted participants' discernment between true and false social-media posts (Prike, Butler, et al, 2023). The authors argued that this effect was in part driven by a correlation between sourcecredibility scores and the veracity of the online post.…”
Section: Don't Believe Them! Reducing Misinformation Influence Throug...supporting
confidence: 87%
“…This is in line with a number of other investigations that included source discreditation alongside contentfocussed corrections as an element of a successful debunking intervention (e.g., MacFarlane et al, 2021;Paynter et al, 2019;Tay et al, 2022). A recent study conducted in a simulated social-media environment found that the presence of source-credibility information boosted participants' discernment between true and false social-media posts (Prike, Butler, et al, 2023). The authors argued that this effect was in part driven by a correlation between sourcecredibility scores and the veracity of the online post.…”
Section: Don't Believe Them! Reducing Misinformation Influence Throug...supporting
confidence: 87%